Acceleration of the Marching Cubes Technique for Volumetric Visualization on Graphics Processing Unit Using Spatial Data Structures - Cirne, Marcos Vinícius Mussel; Pedrini, Hélio (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
Volume rendering has several applications that benefit many domains of knowledge, such as medicine, biology, geology, and virtual reality. One of the most widely used methods for real-time visualization of data volumes is the marching cubes, which is part of a class of visualization techniques called isosurface extraction. Due to the constant evolution of graphics processing units, it is possible to obtain considerable rendering rates and a high degree of realism. This work describes a methodology for accelerating the marching cubes algorithm on a graphics processing unit and presents some possible ways to improve its performance through auxiliary spatial data structures. Experiments using several volumetric datasets show the effectiveness of the proposed method.